The Effects of Antibodies in Disease Progression of MOG-induced Experimental Autoimmune Encephalomyelitis - (:unkn) unknown (My University, 2015)
Abstract: Multiple sclerosis (MS) is an auto-inflammatory disease of the central nervous system (CNS), affecting over 400,000 people in the US. MS is primarily studied in the animal model experimental autoimmune encephalomyelitis (EAE). MS is a T cell mediated disease but there is mounting evidence for a role for B cells in MS. Previous studies have established that rMOG Induction depends on the presence of B cells, while induction using the MOG peptide covering amino acids 35-55 does not require B cells to cause disease. When plasma from the rMOG and MOG35-55 immunized WT mice was analyzed by ELISA there binding at MOG21-45, covering the encephalogenic epitope, and binding covering the MOG46-85 amino acids, which was not expected. This epitope was observed again in T cells when comparing the WT and B cell -/- mice. WT T cells only bound MOG35-55 but T cells from B cell-/- mice also bound MOG61-85. The same epitope observed in WT antibodies. This led to the conclusion that this was a cryptic epitope and seemed to produce an anti-inflammatory response. Mice coimmunized with both MOG35-55 and MOG61-85 similar results were observed as in rMOG immunization. Coimmunized mice had less severe disease than those immunized with just MOG35-55 giving further evidence that MOG61-85 produces a protective response. When rMOG immunized B cell -/- mice were given serum from rMOG primed WT mice clinical disease could be observed. This was also true for coimmunized mice. Meaning it was B cell products in the serum not the B cells themselves that was altering the immune response. When serum from MOG35-55 and MOG61-85 primed rabbit serum was used after heat inactivation, WT and B cell -/- mice showed more severe disease. B cell -/- mice given the immune serum also had an earlier onset of disease. This demonstrated that the most likely cause of the altered response was antibody. Cells from mice coimmunized injected with either immune rabbit serum or preimmune rabbit serum were cultured with MOG35-55 and MOG61-85, proliferation was measured. The mice in the preimmune group had greater proliferation to both peptides. This may be because the encephalogenic cells had already migrated to the CNS in the immune group. When T cells were cultured again with purified antibody, from rMOG primed mice, proliferation decreased in all the wells with antibody added, but when injected into coimmunized mice similar disease was observed as seen in the mice given immune serum. Over all these results indicate a role for antibody in the processing and presentation of MOG in EAE. This may be through the suppression of the presentation of MOG61-85 when antibody is bound to MOG when it is taken up by antigen presenting cells.
Keywords: Antibody; Inflammation; Multiple Sclerosis; Myelin